Biomass antioxidant silica supported tea polyphenols with green and high-efficiency free radical capturing activity for rubber composites. (22nd March 2022) - Guo, Xiaohui; Luo, Yuanfang; Chen, Lijuan; Zhang, Bowen; Chen, Yongjun; Jia, Demin
Abstract: To achieve simultaneous environment protecting, high-efficiency rubber antioxidant is still an enormous and long-term challenge in green rubber industry. Hence, a novel biomass antioxidant (denoted as silica-s-TP) was obtained by silica supported with green tea polyphenols exhibited prominent anti-aging functionality. Silica-s-TP hybrid particles were uniformly dispersed in rubber matrix with remarkable interfacial interaction, and the high-efficiency free radical capturing activity was stem from the construction of polyphenol structure on silica surface. Therefore, silica-s-TP brought to simultaneously enhance the performance of anti-aging property of SBR composites and surpass the achievements of the commercial antioxidants. Interesting, the biomass antioxidant silica-s-TP exhibited remarkable free radical-scavenging activities and stability in SBR matrix than the TP directly added in SBR matrix, due to the chemical anchor TP on silica surface. Such clay surface treatment technology with natural antioxidant may also bring to a new path for the preparation of green and eco-friendly functionalization rubber additives. Graphical abstract: Image 1